(3EfTGA hEOGQI bhGYO GdHjGfGJ HESJNOGe (BAccess xp (3eY OYe deSJNOej (BOffice /s - (3GSeGYjd, eMehOs ((3GdbGgQI(B: s (3OGQ GdcJH GdYdejI ddfTQ hGdJhRjY(B, s, 2003)
(3echfGJ bGYOI GdHjGfGJ(B- (3GdYedjGJ GdCSGSjI Ydi bhGYO GdHjGfGJ(B- (3fXGe EOGQI bhGYO GdHjGfGJ(B- (3GdLOGhd(B- (3GdESJYdGeGJ(B- (3GdfeGPL(B- (3GdJbGQjQ(B.s
(3GdedGMb U(B. 430s
Keywords: (3GdHQeLjGJs; (3Yde GdMGShHs; (3bhGYO GdHjGfGJs